Frequency of TNFA, INFG, and IL10 Gene Polymorphisms and Their Association with Malaria Vivax and Genomic Ancestry - Cruz Furini, Adriana Antonia da; Cassiano, Gustavo Capatti; Capobianco, Marcela Petrolini [UNESP]; Batista dos Santos, Sidney Emanuel; Dantas Machado, Ricardo Luiz [UNESP] (Hindawi Ltd, 2016)
Polymorphisms in cytokine genes can alter the production of these proteins and consequently affect the immune response. The trihybrid heterogeneity of the Brazilian population is characterized as a condition for the use of ancestry informative markers. The objective of this study was to evaluate the frequency of -1031T>C, -308G>A and -238G>A TNFA, +874 A>T IFNG and -819C>T, and -592C>A IL10 gene polymorphisms and their association with malaria vivax and genomic ancestry. Samples from 90 vivax malaria-infected individuals and 51 noninfected individuals from northern Brazil were evaluated. Genotyping was carried out by using ASO-PCR or PCR/RFLP. The genomic ancestry of the individuals was classified using 48 insertion/deletion polymorphism biallelic markers. There were no differences in the proportions of African, European, and Native American ancestry between men and women. No significant association was observed for the allele and genotype frequencies of the 6 SNPs between malaria-infected and noninfected individuals. However, there was a trend toward decreasing the frequency of individuals carrying the TNF-308A allele with the increasing proportion of European ancestry. No ethnic-specific SNPs were identified, and there was no allelic or genotype association with susceptibility or resistance to vivax malaria. Understanding the genomic mechanisms by which ancestry influences this association is critical and requires further study.